Interfaith Dialogue: An Islamic Framework (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
This study analyses the concept of interfaith dialogue, a widely popular issue, from an Islamic perspective with a view to mitigating religious misunderstanding and promoting interfaith harmony. The study adopts qualitative content analysis based on historical elucidations of the Qur’an and the Sunnah. For this purpose, historical documents including both classical and contemporary Islamic literature have been analysed along with recent scholarly journal articles, theses, dissertations, as well as reliable online contents. The findings reveal that Islam accepts interfaith dialogue as a necessary condition for promoting peaceful coexistence and interfaith harmony in every society. The Qur'an has laid a great emphasis on maintaining unity in diversity. The Prophet (PBUH) was a model for mitigating interfaith conflicts throughout his life. Though a few Qur’anic verses seem incongruous with interfaith dialogue and harmony, upon investigation, they are attested to be applied to specific circumstances only. Finally, it concludes that Islam, being a universal religion, plays a unique role in mitigating interfaith encounters and encouraging peaceful coexistence among the followers of different religions and cultures of the world.Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(2), 2023, pp. 193-206